Historia A Debate. Galicia / Xavier Castro ... [et al.] ; Carlos Barrós, editor - Barros, CarlosCastro, Xavier (Congreso Internacional "A Historia a Debate" (1°. 1993. Santiago de Compostela))
Bibliografía